Identification of the Important Genes of Bradyrhizobium diazoefficiens 113-2 Involved in Soybean Nodule Development and Senescence - Yuan, Songli; Zhou, Shunxin; Feng, Yong; Zhang, Chanjuan; Huang, Yi; Shan, Zhihui; Chen, Shuilian; Guo, Wei; Yang, Hongli; Yang, Zhonglu; Qiu, Dezhen; Chen, Haifeng; et al. (Frontiers in Microbiology, 2021)
Legume nodule development and senescence directly affect nitrogen fixation efficiency and involve a programmed series of molecular events. These molecular events are carried out synchronously by legumes and rhizobia. The characteristics and molecular mechanisms of nitrogen fixation at soybean important developmental stages play critical roles in soybean cultivation and fertilizer application. Although the gene expression of soybean were analysed in nodules at five important soybean developmental stages, information on the expression of rhizobial genes in these nodule samples is limited. In the present study, we investigated the expression of Bradyrhizobium diazoefficiens 113-2 genes in the nodule samples from five developmental stages of soybean (Branching stage, flowering stage, fruiting stage, pod stage and harvest stage). Similar gene expression patterns of B. diazoefficiens 113-2 were existed during optimal symbiotic functioning, while different expression patterns were found among early nodule development, nitrogen fixation progress and nodule senescence. Besides, we identified 164 important DEGs associated with nodule development and senescence. These DEGs included those encoding nod, nif, fix proteins and T3SS secretion system-related proteins, as well as proteins involved in nitrogen metabolism, ABC transporters and two-component system pathways. Gene Ontology, KEGG pathway and homology analysis of the identified DEGs revealed that most of these DEGs are uncharacterized genes associated with nodule development and senescence, and they are not core genes among the rhizobia genomes. Our results provide new clues for the understanding of the genetic determinants of soil rhizobia in nodule development and senescence, and supply theoretical basis for the creation of high efficiency soybean cultivation technology.